The Strategy of Smart Shading System in The Residential Building at Surabaya - Syaifuddin Zuhri; Imam Ghozali; Karina Firdauzy (Future Science, 2020)
Climate has a very decisive influence in influencing comfort conditions in space, one of which is its effect on lighting in the room. This lighting performance is greatly influenced by the performance of the openings that allow sunlight to enter the space so that the light intensity in the room can increase. There is a linear relationship between light intensity and aperture, so we need a way to optimize the performance of openings that can be controlled with a shade system or a device that can control the entry of sunlight into space. Active sunshade model or smart shading is one strategy to control incoming sunlight dynamically and to follow changes in light intensity that enters space. This actively adapting shading device is a shading device consisting of a vertical plane consisting of two panels that can move up and down according to the needs of room light intensity. This device is controlled by a control device that gets the light intensity data input from a sensor that is placed in the room to control the light intensity in the room. From the shading device that has been made, it is found that the performance of the device can adapt activities to the light intensity of space ranging from 100-200 lux in daytime conditions with an average panel opening of 12.81-14.42% of the window area.